ESBL Positive Organisms: Method of Routine Reporting and Prevalence in Health Care Settings (Bangladesh Journal of Medical Microbiology, 2017)
Extended Spectrum ß- Lactamase (ESBL) acquired by bacteria is a highly effective weapon for drug resistance against a wide range of antibiotics (penicillins, cephalosporins and monobactams). ESBLs have continued to increase in variety and prevalence and are now a global health concern including Bangladesh. They are associated with failure in effective treatment, increased morbidity and mortality, poor outcomes, increases in length of stay (LOS) in hospital and health care costs. So, it is important to identify it and take necessary measures to treat with appropriate antimicrobial therapy. This study has been designed to establish an easy method for routine reporting of ESBL organisms and notify it's incidence in Health Care settings. Double Disk Diffusion Test, utilizing Cefotaxime, Amoxicillin/Clavulanic acid and Ceftazidime, was used as Screening Test. Phenotypic Confirmatory Test was done for confirmation of screening ESBL positive organisms. Four hundred seventy two organisms (Escherichia coli and Klebsiella sp.) were isolated from urine and pus collected from Health Care settings. Only 50 screening ESBL positive organisms and 50 ESBL negative organisms were tested by Phenotypic Confirmatory Test. All of them were positive and negative respectively by Phenotypic Confirmatory Test. Predominant organism among the isolates was Escherichia coli (82.8%) of which 54.4% were ESBL positive followed by Klebsiella sp. (17.2%) of which 44.4% were ESBL positive. ESBL positivity was more in hospital infections (73.3%) than in community acquiredinfections (44.5%).Bangladesh J Med Microbiol 2014; 08 (02): 23-27